Pemberian Reward dan Punishment untuk Meningkatkan Minat dan Motivasi Belajar Siswa pada Mata Pelajaran Kearsipan Kelas X OTKP SMK Al Washliyah 9 Perbaungan - Khairani (Ikatan Dai Indonesia, 2023)
The purpose of this study is to understand how to increase student motivation and achievement at the X-level math and tata kelola perkantoran in SMK Swasta Al Washliyah 9 Perbaungan by using rewards and sanctions. This study is a PTK (penelitian tindakan kelas) study. This investigation is conducted in two steps, with each step consisting of perencanaan, tindakan execution, observation, and refleksi. The subjects of this study are the 19 students in the SMK Swasta Al Washliyah 9 Perbaungan's Grade X Otomatics and Tata Kelola. Summary data is derived from the number of students, teachers, and available school-related documents. Data collection methods include reviewing observation, testing, documentation, and wawancara results. Method for data validity using method for triangulating set of data. In contrast, data analysis employs scribal and quantitative methods of analysis. According to the results of the study, it can be concluded that using a reward and punishment system can increase student motivation and engagement in the X OTKP class at SMK Swasta Al Washliyah 9 Perbaungan.